Paciente masculino de 25 años con tuberculosis pulmonar. - Vizueta Castillo, Evelin Mercedes (2021)
Tuberculosis is an infectious disease, it is transmitted through the air, it is transmitted from person to person and humans are the only reservoir of the germ, it can cause several symptoms such as: fever, night sweats, weight loss and hemoptysis. Tuberculosis can occur in 3 stages: primary infection, latent infection, and active infection. The most used diagnostic tool for tuberculosis is a simple skin test where a small amount of a substance called tuberculin will be injected and the doctor will check if the injection site on your arm is inflamed, we also find other diagnostic methods are: analysis blood test, sputum exam, and a chest CT scan. All treatment must combine at least 4 drugs not used previously, there must be 2 "essential" drugs, one with good bactericidal activity and the other with good sterilizing capacity, the other two drugs are called "companions" that protect the "essential" drugs ( Isoniazid, Rifampicin, Ethambutol, Pyrazinamide). Treatment should be given for 4 or 7 months and will be terminated by the number of doses taken during a specified period. Among the adverse effects we have the following: loss of appetite, nausea, numbness in the hands and feet, weakness, fatigue, bruising, blurred vision. Patients taking rifampicin should be advised that they will notice an orange tint in their urine.